2015
DOI: 10.1177/0272431615570057
|View full text |Cite
|
Sign up to set email alerts
|

Providing Choice in Middle Grade Classrooms

Abstract: Employing descriptive and interpretive analyses of classroom videos and focus group data, this study details how the provision of choice was enacted in instruction, and the subsequent messages students perceived. Participants included six teachers (fourth to eighth grade) and 114 students (age true X ¯ = 11.28 years, 60% African American). Survey data indicated students perceived high levels of choice in the focal classrooms (Time 1 true X ¯ = 3.32, SD = 0.91; Time 2 true X ¯ = 3.25, SD = 0.94).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The emerging body of research about personalized learning is largely focused on describing these approaches in practice (e.g., Pane, Steiner, Baird, Hamilton, & Pane, 2017;Patrick et al, 2016) and understanding shifts for teachers (e.g., Jobs for the Future and the Council of Chief State School Officers, 2015; Nagle & Taylor, 2017). While there is an emerging body of scholarship examining personalized learning in the middle grades, there is very little written about the perceptions of middle grades students who are engaged in personalized learning (Williams, Wallace, & Sung, 2016). Netcoh (2017), a noteworthy exception, explored middle grades learner perspectives on a personalized learning initiative through focus groups.…”
Section: Learner Perceptions Of Personalized Learningmentioning
confidence: 99%
“…The emerging body of research about personalized learning is largely focused on describing these approaches in practice (e.g., Pane, Steiner, Baird, Hamilton, & Pane, 2017;Patrick et al, 2016) and understanding shifts for teachers (e.g., Jobs for the Future and the Council of Chief State School Officers, 2015; Nagle & Taylor, 2017). While there is an emerging body of scholarship examining personalized learning in the middle grades, there is very little written about the perceptions of middle grades students who are engaged in personalized learning (Williams, Wallace, & Sung, 2016). Netcoh (2017), a noteworthy exception, explored middle grades learner perspectives on a personalized learning initiative through focus groups.…”
Section: Learner Perceptions Of Personalized Learningmentioning
confidence: 99%
“…Existing research on personalized learning has primarily focused on describing its enactment in practice (e.g., Pane, Steiner, Baird, Hamilton, & Pane, 2017;Patrick, Worthen, Frost, & Gentz, 2016) and how it changes teachers' roles and responsibilities in the classroom (e.g., Nagle & Taylor, 2017). There remains a relative lack of research on middle-grade students' experiences with personalized learning, including studies on their perceptions of opportunities for choice in their learning (Williams et al, 2016). In one of the few studies of students' perceptions of personalized learning and choice in their learning in the middle grades, Netcoh (2017) found that students and teachers struggled over the bounds of choice during a newly implemented personalized learning time.…”
Section: Middle Grades Student Perceptions Of Personalized Learningmentioning
confidence: 99%
“…Similarly, Filak and Sheldon (2008) found that students' needsatisfaction increased their likelihood of recommending the course and instructor to friends and their overall evaluation of the course and instructor. Additionally, Williams et al (2015) noted that instructors who offer choices in the classroom communicate trust, respect, and worth to students, which influence their engagement. In other words, allowing students to choose how the lecture will unfold give them ownership over the material and the direction of the learning process.…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…On a daily basis, students make choices regarding their education, such as choosing what classes to take, how to structure their class schedule, which instructors to take/avoid, what extracurricular activities to get involved in, and what major(s) to pursue, among others. In addition to these choices over education, students appreciate their instructors who give them choices in the classroom (Williams, Wallace, & Sung, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation